2018
DOI: 10.1016/j.apmr.2018.04.025
|View full text |Cite
|
Sign up to set email alerts
|

The Adult Assisting Hand Assessment Stroke: Psychometric Properties of an Observation-Based Bimanual Upper Limb Performance Measurement

Abstract: The Ad-AHA Stroke captures actual bimanual performance. Therefore, it provides an additional aspect of upper limb assessment with good to excellent reliability and low SEM for patients with subacute stroke. High convergent validity with the ARA test and UE-FMA and discriminative validity were supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…A higher unit indicates higher ability. Ad-AHA produce a valid measure of bimanual performance 4,5 with good to excellent interrater and intrarater reliability for patients with subacute stroke 5 . In this study, each task was performed at least once by each patient and tasks were alternated between assessment occasions.…”
Section: Main Outcome Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher unit indicates higher ability. Ad-AHA produce a valid measure of bimanual performance 4,5 with good to excellent interrater and intrarater reliability for patients with subacute stroke 5 . In this study, each task was performed at least once by each patient and tasks were alternated between assessment occasions.…”
Section: Main Outcome Assessmentmentioning
confidence: 99%
“…One accelerometerbased study has indicated increased bimanual hand use, during the first 3 months after stroke 3 . Impaired inter-limb coordination 4 and grip force matching between hands 5 have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The ICC was calculated for total scores. ICC is classified as high (more than 0.90), moderate (between 0.75 and 0.90), and low (less than 0.75) (17). To assess the reliability, standard error measurement (SEM) and ICC were used.…”
Section: Discussionmentioning
confidence: 99%
“…A 1–4 category rating scale was used to score the more affected limb on all 19 components: (1) does not do; (2) ineffective; (3) somewhat effective; and (4) effective. The Ad-AHA Stroke has established validity and reliability in individuals post stroke [ 25 ]. All ratings were completed by an experienced and certified rater.…”
Section: Methodsmentioning
confidence: 99%